Cartografia temática do atlas de sensibilidade ambiental a derramamentos de óleo do litoral paulista - Costa, Daiana Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The objective of this paper is the elaboration and implementation of procedures in a cartographic representation related by fundamental of thematic cartography and graphic semiology for the standardization of the Environmental Oil Spill Sensitivity Maps supported by a Geographic Information Systems (GIS) for handling and modeling of a large number of variables. These make up the Environmental Sensitivity Atlas to Oil Spills in Coastal Paulista, and that represents the phenomena that occur in geographic space accurately so as to highlight the importance of each element in the evaluation and protection of areas of greater sensitivity oil. The composition of the cartographic documents considers the Littoral Sensitivity Index (LSI), biological resources and the resources for human use that could be negatively impacted. Thus, the information contained in each map was carefully evaluated before implementation, so that the cartographic representations of various resources, environments, and other ISLs, the reader should issue an immediate message that could be understood clearly, without requiring prior knowledge of specialized. Another aspect was the distribution harmoniously all the elements contained in the document, so that information could be enough without overwhelming it. It was also taken a certain care, so each symbol could be used properly in order that there is no conflict in the information.

Este trabalho tem como objetivo a elaboração e aplicação de procedimentos de representação cartográfica referenciados por fundamentos de cartografia temática e semiologia gráfica para a normalização das Cartas de Sensibilidade Ambiental ao Óleo (Cartas SAO), apoiado por um Sistema de Informação Geográfica (SIG) para a manipulação e modelagem de um grande número de variáveis. As Cartas SAO compõem o Atlas de Sensibilidade Ambiental a derramamentos de óleo do litoral paulista e representam os fenômenos que ocorrem no espaço geográfico de maneira precisa, de modo a evidenciar a importância de cada elemento na avaliação e proteção das áreas de maior sensibilidade ao óleo. A composição dos documentos cartográficos considera o Índice de Sensibilidade do Litoral (ISL), os recursos biológicos e os recursos de uso humano passíveis de serem negativamente impactados. Desta forma, as informações que constam em cada carta foram cuidadosamente avaliadas antes de sua implementação, para que as representações cartográficas dos diversos recursos, ambientes, ISLs e outros, emitissem ao leitor uma mensagem imediata que pudesse ser compreendida claramente, sem demandar conhecimento prévio especializado. Outro aspecto foi a distribuição de forma harmônica de todos os elementos que constam no documento, para que as informações pudessem ser suficientes sem sobrecarregá-lo. Cuidou-se, também, para que cada símbolo fosse convenientemente utilizado de modo a não haver conflito de informações.
Keywords: Geografia; Sistemas de informação geografica; Cartografia temática; Sensibilidade ambiental - Atlas; Cartas SAO; Thematic cartography; Environmental Oil Spill Sensitivity Maps; Atlas; Environmental Sensitivity; Geographic Information Systems